Signal transducer and activator of transcription expression 3 (STAT3) in potentially malignant oral lesions - Monteiro, Maria Carolina de Lima Jacy; Tucci, Renata; Oliveira, Juliana Costa de; Brown, Amy Louise; Araújo, Ney Soares de; Araújo, Vera Cavalcanti de; Furuse, Cristiane (Journal of Oral Diagnosis, 2019)
Objective: The present study evaluated the expression and activation of the STAT-3 in potentially malignant disorders and its association with dysplasia grade. Methods: Twenty-four fragments from two distinct areas, namely the buccal mucosa and the tongue, with 10 cases of hyperkeratosis without dysplasia and 14 cases of hyperkeratosis with mild, moderate or severe dysplasia, were analyzed. Immunohistochemistry for STAT-3 and P-STAT-3 was performed using the biotin-streptavidin-peroxidase method. Results: In both hyperkeratosis with and without dysplasia STAT-3 demonstrated cytoplasmic ex- pression in epithelial layers. Nuclear expression in hyperkeratosis with mild or moderate dysplasia was seen. In hyperkeratosis with severe dysplasia the lower epithelial layers there were areas exhibiting loss of labeling. P-STAT-3 showed nuclear expression in all epithelial layers, except for the superficial layer, in hyperkeratosis without dysplasia. In hyperkeratosis with mild and moderate dysplasia, nuclear expression was seen in all epithelial layers, except for the superficial layer, with a few cells showing no expression. Conclusion: Regarding hyperkeratosis with severe dysplasia, there was loss of expression in a higher number of cells. In both hyperkeratosis with and without dysplasia, STAT-3 activation was found to be abnormal and no significant difference for STAT-3 expression at different dysplasia grades was observed.